Shinta Kamdani: Opportunity and empowering women - Singapore Management University (Institutional Knowledge at Singapore Management University, 2016)
A third-generation entrepreneur, Shinta Kamdani is CEO of her family's Sintesa Group, an Indonesian conglomerate with 6000 employees across 17 companies. Sintesa is a national leader in consumer goods distribution, with other interests in prefab concrete, energy production, steel manufacturing and real estate. Kamdani spoke to Julian Lorkin in Jakarta for BusinessThink.